Calanthe taibaishanensis, A New Orchid Species from China: Evidence from Morphological and Molecular Analyses - Guo, Ming; Zhai, Jun-Wen; Wu, Xin-Yi; Li, Shuang-Xi; Wang, Meng; Li, Zhi-Jun; Chen, Li-Jun (Phytotaxa, 2017)
Calanthe Brown (1821: t. 573) is widely distributed in tropical and subtropical Asia to the Pacific islands and Africa, with only one species distributed in northern South America. Infrageneric relationships of Calanthe and its close related genera, such as Phaius Lour. (1790: t2: 527, 529), Cephalantheropsis Guill. (1960: 188–189) and Gastrorchis Thouars (Gastorkis, 1809: 317) has long been a controversial issue (Xiang et al. 2014; Zhai et al. 2014). A recent treatment suggested was accepted by most orchidologists that both of previously used as subgenus Preptanthe (1853: 245) and section Styloglossum (1829: [11] may well be elevated to the rank of genus (Zhai et al. 2014, Tomohisa Y. & Phillip C. 2014). According to this treatment, the revised Calanthe has about 150 species all over the world, and approximately 40 species in China (Chen et al., 2009; Clayton & Cribb 2013).